Sundheden og det sociale individ. Analyse af to effektiviseringsbegreber - Apollo, Per (Forum for Idræt, 2010)
I artiklen undersøges først statens idealtypiske sundhedsdiskurs og derefter ses på markedet, den historiske udvikling og på aktuelle sundhedsdiskurser. Afslutningsvis kobles den generelle samfundsmæssige udvikling til kroppene i civilsamfundet. Artiklen er videnskabsteoretisk knyttet til Foucaults forståelse af diskurser og praksisregimer. State health policy through history is reflected in contemporary society – as health is used by the state to control and train the population both physically and socially. In addition, the market has evolved into a major player in the health sector, where the market uses state health policy to sell products. Health discourses of the state and the market are a continuation of the overall development of society, from welfare state to a social competition state. Health is important to the competition state in order to succeed in a global world. However, the new configuration of society results in stress, fatigue and obesity in the population. The social differentiation of the population means that the logics of the state and market are translated and adopted in different ways, in diverse communities, and never in their pure forms.